(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: India faces a huge shortfall in procuring blood and young people are ideal candidates for Voluntary Blood Donation (VBD). Experiential learning is active learning by doing and this study explores its role in influencing the Knowledge, Attitude and Behaviour (KAB) of Medical students towards VBD. Aim: To evaluate the effectiveness of experiential learning on VBD behaviour among medical students. Objectives: 1. To assess the changes in the KAB of medical students towards VBD following the intervention. 2. To assess if such changes are retained over a longer period of time (6 months) among the medical students. Settings & Design: Prospective interventional study at NRIIMS, Vizag. Methods and materials: A sample size of 30 was selected by McNemar’s formula for sample calculation. The KAB scores were assessed pre and post intervention. As a part of intervention students were subjected to Experiential Learning by motivating their peers (4) for VBD. The KAB scores were reassessed through delayed post-test after 6 months to know the long term effect. Results: The average score increased from 5.6 to 8.2 for knowledge which was found statistically significant (P<0.0001), from 38.23 to 46. 2 for attitude and practice of blood donation increased significantly from 10% to 66.7% (P<0.0001 in McNemar’s test). The results were consistent even after 6 months in delayed post-test. Conclusion: Experiential learning was successful, improving knowledge, attitude and behaviour towards VBD among students along with retaining the same in long run.